Critical evaluation of the interaction between fluorescent dissolved organic matter and Pb(II) under variable environmental conditions. (November 2022) - Chen, Linwei; Zhuang, Wan-E; Yang, Liyang
Abstract: Dissolved organic matter (DOM) can strongly influence the behavior and risk of metal pollutants in aquatic ecosystems. However, a comprehensive study on the effects of DOM level and environmental factors on the binding of DOM with Pb(II) is lacking. This study examined the DOM-Pb(II) interaction in the river water under variable DOM level, pH, and major ions, using fluorescence excitation-emission matrices-parallel factor analysis (EEMs-PARAFAC). Four humic-like and one protein-like component were identified, and the abundant humic-like components showed higher Pb(II)-binding fractions ( f ) than the protein-like component. The f of PARAFAC components decreased while the conditional stability constants (log K M ) increased for the diluted DOM, indicating the influence of DOM level on its metal binding. The DOM-Pb(II) interaction was sensitive to changes in pH, with generally higher f and lower log K M at the alkaline condition due to changes in the DOM conformation. The addition of major ions significantly decreased the fluorescence quenching by Pb(II), due to competitive effects and potential DOM conformation changes at elevated ions. Overall, our results show that the DOM-Pb(II) complexation is highly dependent on both the DOM properties and environmental factors, which have implications for optimizing the experimental conditions and for comparing the results in different environments. Graphical abstract: Image 1 Highlights: DOM properties and environmental conditions affected the DOM-Pb(II) interaction. Humic-like components had higher binding fractions than the protein-like component. The binding fraction was higher at higher DOM level and under the alkaline condition. The increase of major ions decreased the fraction of DOM complexed with Pb(II). Have implications for comparing the DOM-Pb(II) interaction in different environments.